2021
DOI: 10.7554/elife.67310
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants facilitating the evolution of resistance to carbapenem antibiotics

Abstract: In this era of rising antibiotic resistance, in contrast to our increasing understanding of mechanisms that cause resistance, our understanding of mechanisms that influence the propensity to evolve resistance remains limited. Here, we identified genetic factors that facilitate the evolution of resistance to carbapenems, the antibiotic of 'last resort,' in Klebsiella pneumoniae, the major carbapenem resistant species. In clinical isolates, we found that high-level transposon insertional mutagenesis plays an imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…Our findings along with other data (43, 45, 46) suggest carbapenem non-susceptible Enterobacterales reside along a spectrum mediated to a major degree by changes in porin function and β-lactamase gene copy number. It is likely that unconfirmed CNSE consist of a heterogenous population of ESBL-positive, carbapenem-adapting strains with β-lactamase gene amplifications/porin disruptions which may give different phenotypic results depending on the particular colony tested (47).…”
Section: Discussionsupporting
confidence: 83%
“…Our findings along with other data (43, 45, 46) suggest carbapenem non-susceptible Enterobacterales reside along a spectrum mediated to a major degree by changes in porin function and β-lactamase gene copy number. It is likely that unconfirmed CNSE consist of a heterogenous population of ESBL-positive, carbapenem-adapting strains with β-lactamase gene amplifications/porin disruptions which may give different phenotypic results depending on the particular colony tested (47).…”
Section: Discussionsupporting
confidence: 83%
“…The idea of transposon insertional mutagenesis as a means of resistance acquisition is not completely novel but is not yet well investigated. Transposon insertional mutagenesis has been described to play an important role in contributing to high-level resistance toward ertapenem ( 27 ). In their experiments, Ma et al ( 27 ) demonstrated that a reversible transposon insertion into the ompK36 gene, encoding one of the major porins of Klebsiella pneumoniae , could be identified in ertapenem-resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Transposon insertional mutagenesis has been described to play an important role in contributing to high-level resistance toward ertapenem ( 27 ). In their experiments, Ma et al ( 27 ) demonstrated that a reversible transposon insertion into the ompK36 gene, encoding one of the major porins of Klebsiella pneumoniae , could be identified in ertapenem-resistant isolates. In contrast, in our case, the cefiderocol resistance was not reverted by serial passaging in the absence of antibiotic pressure, indicating the stability of the transposon insertion (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that bla ESBL genes such as bla CTX-M or bla SHV-5 in combination with outer membrane porin deficits can cause carbapenem resistance in K. pneumoniae isolates that do not coharbor carbapenemase genes ( 13 , 14 ). Similarly, bla ESBL gene duplications have been shown to increase carbapenem MICs in isolates without a carbapenemase ( 46 ). However, the present study suggests, for the first time, that neither the presence of an bla ESBL nor the bla ESBL gene copy number appreciably increases the carbapenem MICs in isolates that coharbor carbapenemase genes, which is supported by the absence of these genomic features in the final multivariate models.…”
Section: Discussionmentioning
confidence: 99%